Synaptic Organization of Microglomerular Clusters in the Lateral and Medial Bulbs of the Honeybee Brain - Mota, Theo; Kreissl, Sabine; Carrasco Durán, Ana; Lefer, Damien; Galizia, Giovanni; Giurfa, Martin (Frontiers in Neuroanatomy, 2016)
The honeybee Apis mellifera is an established model for the study of visual orientation. Yet, research on this topic has focused on behavioral aspects and has neglected the investigation of the underlying neural architectures in the bee brain. In other insects, the anterior optic tubercle (AOTU), the lateral (LX) and the central complex (CX) are important brain regions for visuospatial performances. In the central brain of the honeybee, a prominent group of neurons connecting the AOTU with conspicuous microglomerular synaptic structures in the LX has been recently identified, but their neural organization and ultrastructure have not been investigated. Here we characterized these microglomerular structures by means of immunohistochemical and ultrastructural analyses, in order to evaluate neurotransmission and synaptic organization. Three-dimensional reconstructions of the pre-synaptic and post-synaptic microglomerular regions were performed based on confocal microscopy. Each pre-synaptic region appears as a large cup-shaped profile that embraces numerous post-synaptic profiles of GABAergic tangential neurons connecting the LX to the CX. We also identified serotonergic broad field neurons that probably provide modulatory input from the CX to the synaptic microglomeruli in the LX. Two distinct clusters of microglomerular structures were identified in the lateral bulb (LBU) and medial bulb (MBU) of the LX. Although the ultrastructure of both clusters is very similar, we found differences in the number of microglomeruli and in the volume of the pre-synaptic profiles of each cluster. We discuss the possible role of these microglomerular clusters in the visuospatial behavior of honeybees and propose research avenues for studying their neural plasticity and synaptic function.